Medical conditions affecting pregnancy and childbirth - Bothamley, Judy; Bothamley, Judy; Boyle, Maureen (London : Routledge, 2021)
Midwives are encountering more and more women whose highly pregnancies are complicated by medical conditions. This second edition is completely up-to-date and offers highly practical solutions for everyday practice.
Includes bibliographical references and index.
Keywords: Pregnancy Complications; Pregnancy; Parturition